Exposição de fibroblastos da cápsula de Tenon normal de portadores de pterígio ao 5-fluorouracil e à mitomicina C - Viveiros, Magda Massae Hata [UNESP] (2007)
Purpose: To evaluate the fibroblast proliferation activity of normal Tenon's capsule from primary and recurrent patients with pterygium. Methods: A randomized prospective study was performed with 41 normal Tenon's capsule fragments from 21 primary and 20 recurrent patients with pterygium. The sample was collected from the inferior cul-de-sac. Proliferation rate from fibroblasts were evaluated after mitomycin C and 5-fluorouracil exposition. Data were submitted to statistical analysis. Results: Of the 41 cultivated normal Tenon's capsules, only 1 from primary and 2 from recurrent pterygium patients proliferated. After antimitotic exposition, the proliferation rate was similar with both drugs. Conclusion: Mitomycin and 5-fluorouracil promote similar inhibition regarding proliferation of normal Tenon's fibroblast cultures.